Hemodynamic Functionality of Transfused Red Blood Cells in the Microcirculation of Blood Recipients - Barshtein, Gregory; Arbell, Dan; Yedgar, Saul (Frontiers in Physiology, 2018)
Red blood cell (RBC) transfusion is a life-saving procedure whose primary objective is to sustain tissue and organ oxygenation. However, there is growing concern regarding the risks in the transfusion of packed red blood cells (PRBC), as numerous studies have reported negative transfusion outcomes, including reduced blood perfusion. RBC have unique flow-affecting properties, specifically adherence to blood vessel wall endothelium, cell deformability, and self-aggregability, which define their hemodynamic functionality (HF), namely their potential to affect blood circulation. The role of the HF of RBC in blood circulation, particularly the microcirculation, has been documented in numerous studies with animal models. These studies indicate that the HF of transfused RBC (TRBC) is an important determinant of the transfusion outcome. However, animal studies must be interpreted with a number of caveats, as animal biology may not reflect human biology. To test this concept in humans, we have directly examined the effect of the HF of TRBC, as expressed by their deformability and adherence to vascular endothelium, on the transfusion-induced change in the skin blood flow and hemoglobin increment in blood recipients. The results demonstrated, for the first time in humans, that the HF of TRBC transfused of β-thalassemia major patients is a potent effector of the transfusion outcome, as expressed by the transfusion-induced change in the recipients` skin blood flow and hemoglobin increment, which indicates a link between the microcirculation and the survival of TRBC in the recipients’ vascular system. The implication of these findings for blood transfusion practice to vascular function is discussed.